Characteristics and alteration of pesticide residues in surface soils of agricultural fields and public parks - Al-Mutlaq, Khalid F (Environmental earth sciences, 2006)
Organic contents of agricultural soils are major sources of organic compounds and pesticides into atmosphere. Therefore, surface soil samples from different locations in the city of Corvallis, USA were collected over a course of 1 year (2004/2005). The samples were subject to chemical extraction and analysis by gas chromatography-mass spectrometry (GC-MS). The results of the chemical analysis showed pesticide residues were present in soils and varied seasonally. For example, the highest total relative concentration of pesticide residues in Canola field was 0.16% in January 2005, and was 0.56% in Wheat Field in August 2005, and was 0.14% in the River Front Park in December 2004 and was 0.33 in Rose Garden. Sometimes in the year, these pesticide residues were not detected in the same sites.